SOME METHODS OF WORKING WITH CONCEPTS AND TERMS IN HISTORY LESSONS (World Bulletin of Education and Learning, 2025)
This article discusses the study and systematization of methods, ways and means of forming concepts in the process of teaching history at all stages of education. Also, to determine the role of historical concepts in the study of history, to highlight the features of the formation of concepts in the process of teaching history.
Keywords: Learning, term, terminology, concepts, continuing education, method, formations, competence, history lessons.